Analysis of National Legislation on Conflict of Interest Regulation (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article provides a detailed analysis of the national legislation of the Republic of Uzbekistan regulating conflicts of interest and its effectiveness. The report examines the concept of conflict of interest, prevention mechanisms, duties of state bodies and officials, as well as existing control and accountability measures. The analysis results aim to identify legislative shortcomings and ways to improve them, which is crucial for effective anti-corruption efforts.